Astrophysical Aspects of Neutrino Dynamics in Ultradegenerate Quark Gluon Plasma - Souvik Priyam Adhya (Advances in High Energy Physics)
The cardinal focus of the present review is to explore the role of neutrinos originating from the ultradense core of neutron stars composed of quark gluon plasma in the astrophysical scenario. The collective excitations of the quarks involving the neutrinos through the different kinematical processes have been studied. The cooling of the neutron stars as well as pulsar kicks due to asymmetric neutrino emission has been discussed in detail. Results involving calculation of relevant physical quantities like neutrino mean free path and emissivity have been presented in the framework of non-Fermi liquid behavior as applicable to ultradegenerate plasma.